The coquette - Foster, Hannah Webster, 1759-1840 ([s.n.], 2013)
The Coquette tells the much-publicized story of the seduction and death of Elizabeth Whitman, a poet from Hartford, Connecticut. Written as a series of letters--between the heroine and her friends and lovers--it describes her long, tortuous courtship by two men, neither of whom perfectly suits her. Eliza Wharton (as Whitman is called in the novel) wavers between Major Sanford, a charming but insincere man, and the Reverend Boyer, a bore who wants to marry her. When, in her mid-30s, Wharton finds herself suddenly abandoned when both men marry other women, she willfully enters into an adulterous relationship with Sanford and becomes pregnant. Alone and dejected, she dies in childbirth at a roadside inn. Eliza Wharton, whose real-life counterpart was distantly related to Hannah Foster's husband, was one of the first women in American fiction to emerge as a real person facing a dilemma in her life. In her Introduction, Davidson discusses the parallels between Elizabeth Whitman and the fictional Eliza Wharton. She shows the limitations placed on women in the 18th century and the attempts of one woman to rebel against those limitations.